'A discussion forum': a blended learning assessment tool to enhance students' learning. (1st January 2014) - Miniaoui, Hela; Kaur, Avneet
The term 'blended learning' has gained considerable interest in recent years as a description of particular forms of teaching combined with technology. This project reports in some detail the experiences of a small group of undergraduate learners as they progress through their Bachelor course at University of Wollongong in Dubai (UOWD) in the UAE. In particular, this study looks at a discussion forum approach as a blended learning initiative and what that entails to the learners in terms of making the subject more interactive and enhances students analytical and research skills. From the findings, conclusion has been drawn regarding the role of blackboard tool in learning by helping students to obtain a deep sense of understanding of how to operate in a virtual team despite the challenges.